Taxonomic status of the genera Amphipholizona H.L. Clark, 1915 (Ophiuroidea, Ophiolepididae) and Amphigyptis Nielsen, 1932 (Hemieuryalidae): systematic placement and synonymy - Gondim, Anne Isabelley; Christoffersen, Martin Lindsey; Dias, Thelma Lúcia Pereira; Solís, Francisco Alonso -Marín (Zootaxa, 2016)
We synonymize Amphipholizona (Ophiolepididae) and Amphigyptis (Hemieuryalidae), suggest their transfer to family Amphiuridae, and propose a new species combination (Amphipholizona perplexa new comb.). We further provide a new diagnosis for the genus Amphipholizona, a dichotomic identification key for the two species now belonging to this genus and re-describe and illustrate for the first time some of the internal characters, such as the genital plates, vertebrae, and inner side of the lateral arm plate.